Analysis of the Level of Knowledge about DAGUSIBU for Housewives, Bukit Barisan District, Pekanbaru City - Syafitri, Ikke (Integrative Perspectives of Social and Science Journal, 2026)
DAGUSIBU is a program created or organized from Indonesian Pharmacists Association (IAI), which stands for acquire, use, store and dispose medicine properly. DAGUSIBU is an important matter that the public must know to prevent mistakes and improve public health rates, especially among housewives, and in fostering rational drug use. The implementation method of the activity is carried out through socialization or counseling and also includes free health checks. The results of activities conducted with housewives showed a fairly high percentage. Thus, can be drawn a line if the socialization is carried out plays a very important role and also provides benefits.